Separation of Ho3+ in Static Magnetic Field - Kołczyk K.; Wojnicki M.; Kutyła D.; Kowalik R.; Żabiński P.; Cristofolini A. (Archives of Metallurgy and Materials, 2016)
The rare earths elements (REE) belong to the group of critical metals and they are achieving more and more interest due to their special properties. However, there occur some problems connected with their production. The most difficult phase is separation of REE. It includes a necessity to intensify currently applied processes and looking for new solutions.